Low odor low emission styrene-based tpe material for automotive interior and preparation method thereof

CN122978734APending Publication Date: 2026-10-27ANHUI ZHONGHAN POLYMER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611319801.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,该后处理方法存在明显局限性:一方面,热处理温度和时间受材料耐热性制约,过度处理会导致材料力学性能劣化,因此对气味分子的脱除效率有限;另一方面,石化基弹性体材料中低分子挥发物的释放是一个持续、缓慢的过程,单纯的加速散发难以彻底消除其在长期使用中的累积释放风险,对于气味等级要求严苛的项目往往难以达标

Benefits of technology

本发明的改性吸附助剂通过有机改性层的分子结构设计,同步实现无机填料的高效分散、加工过程气味吸附及材料力学与阻燃性能的提升。3-甲氧基-4-羟基苯甲醛的酚羟基与甲基丙烯酸缩水甘油酯的环氧基团经开环醚化反应,在中间体A中引入可聚合双键及刚性苯环结构;再经席夫碱反应接枝硅烷偶联剂,并经亚磷酸二乙酯磷酸化引入磷系阻燃基团,制得有机改性剂。该改性剂通过硅烷偶联剂与活性炭、白炭黑、氧化铝、沸石粉等多孔填料表面羟基化学键合,形成有机包覆层。该有机层因含有苯环、双键及长链烷基结构,与SEBS分子链中的苯乙烯嵌段及聚丙烯链段具有优良的相似相容性,显著改善无机填料在基体中的分散均匀性与界面亲和性,避免团聚引发的应力集中,使材料拉伸强度和冲击韧性明显增强;同时多孔载体在熔融共混阶段即对加工过程产生的小分子挥发物进行物理吸附捕获,减少气味物质残留;引入的亚磷酸二乙酯结构在燃烧时促进致密炭层生成,赋予材料良好阻燃性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1787899150595-000001
    Figure REF-OBJ-1787899150595-000001
  • Figure REF-OBJ-1787899150595-000002
    Figure REF-OBJ-1787899150595-000002
Patent Text Reader

Abstract

The application discloses a low-odor and low-emission styrene TPE material for automobile interior decoration and a preparation method thereof, and belongs to the technical field of high polymer materials. The material is prepared from SEBS, white oil, hydrogen-regulated polypropylene, modified adsorption additives, fillers and antioxidants by double-screw melt extrusion, and a devolatilization additive is injected at the tail end of extrusion. The modified adsorption additive is formed by chemically coating a porous carrier such as activated carbon with an organic modifier containing a benzene ring, a double bond and a phosphorus group, which can improve the dispersibility of inorganic fillers in the matrix and adsorb and capture small molecular volatile substances in the melt blending stage. Meanwhile, hydrogen-regulated polypropylene is selected to replace traditional degradation varieties to reduce aldehyde and ketone by-products from the source, and the devolatilization additive in the extrusion process is used to extract residual low molecular substances, so that the odor and VOC control in the whole process are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to low-odor, low-emission styrene-based TPE materials for automotive interiors and their preparation methods. Background Technology

[0002] Currently, thermoplastic elastomers (TPEs) are widely used in automotive interior elastomer materials due to their excellent flexibility, resilience, and processability. As consumers become increasingly concerned about in-vehicle air quality, OEMs are imposing stricter requirements on low odor and low volatile organic compound (VOC) emissions from automotive interior materials. Especially in the high-standard projects for new models, the odor level and total carbon emissions of materials have become key performance indicators.

[0003] To reduce the odor and emission performance of materials, the industry commonly employs a post-treatment process involving high-temperature, long-duration hot air drying, attempting to accelerate the release of residual small-molecule volatiles from the material through thermo-oxidative aging. However, this post-treatment method has significant limitations: firstly, the heat treatment temperature and time are constrained by the material's heat resistance, and excessive treatment can lead to deterioration of the material's mechanical properties, thus limiting the efficiency of odor removal; secondly, the release of low-molecular-weight volatiles from petrochemical-based elastomer materials is a continuous and slow process, and simply accelerating emission cannot completely eliminate the risk of cumulative release during long-term use, often failing to meet the standards for projects with stringent odor level requirements. Therefore, the industry has gradually recognized that relying solely on post-treatment methods cannot fundamentally solve the emission problem.

[0004] To address the aforementioned technical bottlenecks, a key research direction is to develop material systems capable of in-situ extraction and removal of low-molecular-weight odor sources during processing, or to endow materials with highly efficient adsorption capabilities for small-molecule volatiles, thereby achieving source control and process elimination of odor substances during the material forming stage. However, existing technologies mostly focus on optimizing post-processing parameters, while systematic research on simultaneously achieving volatile adsorption, extraction, and removal during melt processing is limited. There is a lack of effective solutions that simultaneously improve odor generation and removal from the perspective of material composition design and synergistic processing technology. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and to provide a low-odor, low-emission styrene-based TPE material for automotive interiors and its preparation method.

[0006] The objective of this invention can be achieved through the following technical solutions: A method for preparing low-odor, low-emission styrene-based TPE materials for automotive interiors includes the following steps: mixing SEBS, white oil, hydrogen-modified polypropylene, modified adsorption aid, filler, and antioxidant, stirring evenly, feeding into a twin-screw extruder, melt extruding, granulating, injecting devolatilization aid at the rear end of the twin-screw near the vacuum port, and then granulating, drying, and homogenizing to obtain styrene-based TPE materials.

[0007] More preferably, the styrene-based TPE material comprises the following components by weight: 10-30 parts SEBS, 20-50 parts white oil, 10-20 parts hydrogen-modified polypropylene, 3-5 parts modified adsorption and devolatilization aid, 24-30 parts filler, and 0.5-1 part antioxidant.

[0008] In a more optimized manner, the preparation process of the modified adsorption aid is as follows: S1: Under a protective atmosphere, 3-methoxy-4-hydroxybenzaldehyde, 2,3-epoxypropyl methacrylate, and anhydrous ethanol were mixed and stirred until homogeneous. Tetrabutylammonium bromide was added, the temperature was raised to 85°C, and the mixture was stirred at a constant temperature for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, and the cooled solution was transferred to a low-temperature environment for crystallization. The crystallized system was filtered, the filter cake was collected, and after drying, intermediate A was obtained. S2: Under a protective atmosphere, intermediate A was added to anhydrous N,N-dimethylformamide and stirred until homogeneous. Then, γ-aminopropyltriethoxysilane solution was slowly added dropwise. After the addition was complete, the temperature was raised to 70°C and the mixture was stirred at a constant temperature for 12 hours. Then, diethyl phosphite was added, the temperature was raised to 90-85°C, and the mixture was stirred for another 14 hours. After the reaction was completed, the mixture was cooled to room temperature, and the solvent was removed by rotary evaporation. The concentrated solution was slowly added dropwise to a large amount of deionized water, and the solid precipitated. The solid was filtered, washed, and dried to obtain the modifier. S3: Activated carbon, silica, alumina, and zeolite powder were added to a mixed solvent of anhydrous ethanol and deionized water. After ultrasonic dispersion, the pH was adjusted to 4-5 with acetic acid to obtain a mixed suspension. The modifier was added to anhydrous ethanol and stirred until homogeneous. Then, it was slowly added to the mixed suspension at room temperature. After the addition was complete, the temperature was raised to 60°C and the reaction was carried out with constant temperature and stirring for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with anhydrous ethanol and deionized water in sequence, and vacuum dried to obtain the modified adsorption aid.

[0009] The structure of the modifier is shown below:

[0010] In a more optimized manner, the raw materials for preparing intermediate A include the following components: by weight, 10-12 parts of 3-methoxy-4-hydroxybenzaldehyde, 9-10 parts of 2,3-epoxypropyl methacrylate, 70-80 parts of anhydrous ethanol, and 0.3-0.5 parts of tetrabutylammonium bromide.

[0011] In a more optimized manner, the raw materials for preparing the modifier include the following components: by weight, 10-12 parts of intermediate A, 60-80 parts of anhydrous N,N-dimethylformamide, 18-19 parts of γ-aminopropyltriethoxysilane solution, and 4-5 parts of diethyl phosphite; wherein the concentration of the γ-aminopropyltriethoxysilane solution is 40 wt%.

[0012] In a more optimized manner, the raw materials for preparing the modified adsorption aid include the following components: by weight, 30-40 parts activated carbon, 20-25 parts silica, 10-15 parts alumina, 10-15 parts zeolite powder, 180-250 parts anhydrous ethanol, 80-100 parts deionized water, and 10-12 parts modifier.

[0013] More optimally, the devolatilization aid comprises deionized water and anhydrous ethanol in a mass ratio of 1:1.

[0014] More preferably, the antioxidant is one or more of B215, 1010, 1076, 1790, and 168.

[0015] The beneficial effects of this invention are: The modified adsorbent of this invention achieves efficient dispersion of inorganic fillers, adsorption of odors during processing, and improvement of material mechanical and flame-retardant properties through the molecular structure design of an organic modified layer. The phenolic hydroxyl group of 3-methoxy-4-hydroxybenzaldehyde and the epoxy group of glycidyl methacrylate undergo a ring-opening etherification reaction to introduce polymerizable double bonds and a rigid benzene ring structure into intermediate A. Then, a silane coupling agent is grafted via a Schiff base reaction, and a phosphorus-based flame-retardant group is introduced via diethyl phosphite phosphorylation to obtain the organic modifier. This modifier chemically bonds to the hydroxyl groups on the surface of porous fillers such as activated carbon, silica, alumina, and zeolite powder through a silane coupling agent, forming an organic coating layer. The organic layer, containing benzene rings, double bonds, and long-chain alkyl structures, exhibits excellent compatibility with the styrene blocks and polypropylene segments in the SEBS molecular chain. This significantly improves the dispersion uniformity and interfacial affinity of the inorganic filler in the matrix, avoids stress concentration caused by agglomeration, and substantially enhances the tensile strength and impact toughness of the material. Simultaneously, the porous carrier physically adsorbs and captures small-molecule volatiles generated during the melt blending stage, reducing odor residue. The introduced diethyl phosphite structure promotes the formation of a dense char layer during combustion, endowing the material with good flame-retardant properties.

[0016] Furthermore, at the source, this invention selects hydrogen-modified polypropylene instead of traditional peroxide degradation varieties. Its molecular weight control does not involve peroxide decomposition, avoiding the generation of aldehyde and ketone byproducts and fundamentally suppressing the release of volatile small molecules during processing and heating. At the end, a devolvation aid consisting of deionized water and anhydrous ethanol is injected at the rear end of the twin-screw extruder. This extractant penetrates into the material under high temperature and vacuum, dissolving and carrying away residual small volatile molecules, which are then completely removed through vacuum negative pressure and subsequent drying processes. Through this comprehensive chain control, the material's odor level and VOC content are significantly reduced, fully meeting the stringent requirements of automotive interiors for low emissions, high strength and toughness, and flame retardant safety. Detailed Implementation

[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0018] It should be noted that the following parts are by weight, and there are no special restrictions on the manufacturers of the raw materials involved in this invention. Exemplary examples include: SEBS grade 6151, manufactured by Huizhou Li Changrong; white oil grade 2266, manufactured by Hansheng; hydrogen-modified polypropylene grade BX3900, manufactured by XK Group of South Korea; calcium carbonate as filler; and B215 as antioxidant.

[0019] Example 1: A method for preparing a low-odor, low-emission styrene-based TPE material for automotive interiors, comprising the following steps: mixing 20 parts SEBS, 40 parts white oil, 10 parts hydrogen-modified polypropylene, 24.5 parts calcium carbonate, 5 parts modified adsorption agent, and 0.5 parts antioxidant, stirring evenly, feeding into a twin-screw extruder, melt extruding, granulating, and adding a 1:1 mixture of water and ethanol accounting for 0.5% of the total material mass in the formula to a section before the vacuum port, then granulating, drying and homogenizing to obtain the styrene-based TPE material; The preparation process of the modified adsorption-devouring aid is as follows: S1: Under a protective atmosphere, 10 parts of 3-methoxy-4-hydroxybenzaldehyde, 9 parts of 2,3-epoxypropyl methacrylate, and 70 parts of anhydrous ethanol were mixed and stirred evenly. Then, 0.3 parts of tetrabutylammonium bromide were added, the temperature was raised to 85°C, and the mixture was stirred at a constant temperature for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, and the cooled solution was transferred to a low-temperature environment for crystallization. The crystallized system was filtered, the filter cake was collected, and after drying, intermediate A was obtained. S2: Under a protective atmosphere, 10 parts of intermediate A were added to 60 parts of anhydrous N,N-dimethylformamide. After stirring evenly, 18 parts of γ-aminopropyltriethoxysilane solution (concentration 40wt%) were slowly added dropwise. After the addition was complete, the temperature was raised to 70℃ and the reaction was stirred at a constant temperature for 12h. Then, 4 parts of diethyl phosphite were added, the temperature was raised to 90-85℃, and the reaction was stirred for another 14h. After the reaction was completed, the temperature was cooled to room temperature, the solvent was removed by rotary evaporation, and the concentrated solution was slowly added dropwise to a large amount of deionized water to precipitate the solid. The solid was filtered, washed, and dried to obtain the modifier. S3: Add 30 parts activated carbon, 20 parts silica, 10 parts alumina, and 10 parts zeolite powder to a mixed solvent of 100 parts anhydrous ethanol and 80 parts deionized water. After ultrasonic dispersion, adjust the pH to 4-5 with acetic acid to obtain a mixed suspension. Add 10 parts modifier to 80 parts anhydrous ethanol and stir well. Then, slowly add the modifier to the mixed suspension at room temperature. After the addition is complete, raise the temperature to 60°C and stir continuously at a constant temperature for 4 hours. After the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol and deionized water in sequence, and vacuum dry to obtain the modified adsorption and devolatilization aid.

[0020] Example 2: A method for preparing a low-odor, low-emission styrene-based TPE material for automotive interiors, comprising the following steps: mixing 20 parts SEBS, 40 parts white oil, 10 parts hydrogen-modified polypropylene, 25.5 parts calcium carbonate, 4 parts modified adsorption agent, and 0.5 parts antioxidant, stirring evenly, and then feeding the mixture into a twin-screw extruder for melt extrusion and granulation. A 1:1 mixture of water and ethanol, accounting for 0.5% of the total material mass, is added to the section before the vacuum inlet. The mixture is then granulated, dried, and homogenized to obtain the styrene-based TPE material. The preparation process of the modified adsorption-devouring aid is as follows: S1: Under a protective atmosphere, 12 parts of 3-methoxy-4-hydroxybenzaldehyde, 10 parts of 2,3-epoxypropyl methacrylate, and 80 parts of anhydrous ethanol were mixed and stirred evenly. Then, 0.5 parts of tetrabutylammonium bromide were added, the temperature was raised to 85°C, and the mixture was stirred at a constant temperature for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, and the cooled solution was transferred to a low-temperature environment for crystallization. The crystallized system was filtered, the filter cake was collected, and after drying, intermediate A was obtained. S2: Under a protective atmosphere, 12 parts of intermediate A were added to 80 parts of anhydrous N,N-dimethylformamide. After stirring evenly, 19 parts of γ-aminopropyltriethoxysilane solution (concentration 40wt%) were slowly added dropwise. After the addition was completed, the temperature was raised to 70℃ and the reaction was stirred at a constant temperature for 12h. Then, 5 parts of diethyl phosphite were added, the temperature was raised to 90-85℃, and the reaction was stirred for another 14h. After the reaction was completed, the mixture was cooled to room temperature, the solvent was removed by rotary evaporation, and the concentrated solution was slowly added dropwise to a large amount of deionized water to precipitate the solid. The solid was filtered, washed, and dried to obtain the modifier. S3: Add 40 parts activated carbon, 25 parts silica, 15 parts alumina, and 15 parts zeolite powder to a mixed solvent of 150 parts anhydrous ethanol and 100 parts deionized water. After ultrasonic dispersion, adjust the pH to 4-5 with acetic acid to obtain a mixed suspension. Add 12 parts modifier to 100 parts anhydrous ethanol and stir well. Then, slowly add the modifier to the mixed suspension at room temperature. After the addition is complete, raise the temperature to 60°C and stir continuously at a constant temperature for 4 hours. After the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol and deionized water in sequence, and vacuum dry to obtain the modified adsorption and devolatilization aid.

[0021] Example 3: A method for preparing a low-odor, low-emission styrene-based TPE material for automotive interiors, comprising the following steps: mixing 20 parts SEBS, 40 parts white oil, 10 parts hydrogen-modified polypropylene, 26.5 parts calcium carbonate, 3 parts modified adsorption agent, and 0.5 parts antioxidant, stirring evenly, and then feeding the mixture into a twin-screw extruder for melt extrusion and granulation. A 1:1 mixture of water and ethanol, accounting for 0.5% of the total material mass, is added to the section before the vacuum port. The mixture is then granulated, dried, and homogenized to obtain the styrene-based TPE material. The preparation process of the modified adsorption-devouring aid is as follows: S1: Under a protective atmosphere, 11 parts of 3-methoxy-4-hydroxybenzaldehyde, 9.5 parts of 2,3-epoxypropyl methacrylate, and 75 parts of anhydrous ethanol were mixed and stirred evenly. Then, 0.4 parts of tetrabutylammonium bromide were added, the temperature was raised to 85°C, and the mixture was stirred at a constant temperature for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, and the cooled solution was transferred to a low-temperature environment for crystallization. The crystallized system was filtered, the filter cake was collected, and after drying, intermediate A was obtained. S2: Under a protective atmosphere, 11 parts of intermediate A were added to 70 parts of anhydrous N,N-dimethylformamide. After stirring evenly, 18.5 parts of γ-aminopropyltriethoxysilane solution (concentration 40wt%) were slowly added dropwise. After the addition was complete, the temperature was raised to 70℃ and the reaction was stirred at a constant temperature for 12 hours. Then, 4.5 parts of diethyl phosphite were added, the temperature was raised to 90-85℃, and the reaction was stirred for another 14 hours. After the reaction was completed, the mixture was cooled to room temperature, the solvent was removed by rotary evaporation, and the concentrated solution was slowly added dropwise to a large amount of deionized water. The solid precipitated, filtered, washed, and dried to obtain the modifier. S3: Add 35 parts activated carbon, 22.5 parts silica, 12.5 parts alumina, and 12.5 parts zeolite powder to a mixed solvent of 125 parts anhydrous ethanol and 90 parts deionized water. After ultrasonic dispersion, adjust the pH to 4-5 with acetic acid to obtain a mixed suspension. Add 11 parts modifier to 90 parts anhydrous ethanol and stir well. Then, slowly add the modifier to the mixed suspension at room temperature. After the addition is complete, raise the temperature to 60°C and stir continuously at a constant temperature for 4 hours. After the reaction is complete, cool to room temperature, filter, wash with anhydrous ethanol and deionized water in sequence, and vacuum dry to obtain the modified adsorption and devolatilization aid.

[0022] Comparative Example 1: No modification was made to the adsorption and devolatilization aid, as detailed below: A method for preparing low-odor, low-emission styrene-based thermoplastic elastomer materials for automotive interiors includes the following steps: mixing 20 parts SEBS, 40 parts white oil, 10 parts hydrogen-modified polypropylene, 24.5 parts calcium carbonate, 5 parts adsorption aids (activated carbon, silica, alumina, and zeolite powder in a mass ratio of 3:2:1:1), and 0.5 parts antioxidant, stirring evenly, and then feeding the mixture into a twin-screw extruder for melt extrusion and granulation. A 1:1 mixture of water and ethanol, accounting for 0.5% of the total material mass, is added to the section before the vacuum inlet. The mixture is then granulated, dried, and homogenized to obtain the styrene-based TPE material.

[0023] Comparative Example 2: No modified adsorption agent was added, as detailed below: A method for preparing a low-odor, low-emission styrene-based thermoplastic elastomer material for automotive interiors includes the following steps: mixing 20 parts SEBS, 40 parts white oil, 10 parts hydrogen-modified polypropylene, 24.5 parts calcium carbonate, and 0.5 parts antioxidant, stirring evenly, and then feeding the mixture into a twin-screw extruder for melt extrusion and granulation. A 1:1 mixture of water and ethanol, accounting for 0.5% of the total material mass, is added to the section before the vacuum inlet. The mixture is then granulated, dried, and homogenized to obtain the styrene-based TPE material.

[0024] Testing experiment: (1) The tensile strength of the finished products obtained in the examples and comparative examples was tested in accordance with standard ISO 527-1; (2) The hardness of the finished products obtained in the examples and comparative examples was tested according to the standard ASTM D2240; (3) The odor of the material shall be evaluated in accordance with Q / SQR T1-8.4-2025; (4) The limiting oxygen index of the material was tested according to GB / T 2406.2-2009; The obtained data is shown in the table below:

[0025] Conclusion: Comparison of the test data from the examples and comparative examples shows that the styrene-based thermoplastic elastomer material prepared by this invention is significantly superior to the control sample without modified adsorption agents or without added agents in terms of tensile strength, hardness, odor level, and limiting oxygen index. Example 1 achieved an odor level of 2.5, a limiting oxygen index of 27.5%, and a tensile strength of 15.2 MPa, indicating that the modified adsorption agent effectively improves filler dispersion and enhances mechanical properties. Simultaneously, it synergistically controls volatile substances from both the source and end of the process with hydrogen-modified polypropylene and devolatilization aids, significantly reducing odor and VOC residues and imparting good flame retardancy to the material. Overall, this invention, through full-chain optimization of material composition and processing technology, successfully meets the stringent requirements of automotive interior materials for low odor, low emissions, high strength and toughness, and flame retardant safety.

[0026] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0027] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing low-odor, low-emission styrene-based TPE materials for automotive interiors, characterized in that, The process includes the following steps: mixing SEBS, white oil, hydrogen-modified polypropylene, modified adsorption aid, filler, and antioxidant, stirring evenly, feeding into a twin-screw extruder, melt extruding, granulating, injecting devolatilization aid at the rear end of the twin-screw near the vacuum port, and then granulating, drying, and homogenizing to obtain styrene-based TPE material.

2. The method for preparing low-odor, low-emission styrene-based TPE material for automotive interiors according to claim 1, characterized in that, The styrene-based TPE material comprises the following components by weight: 10-30 parts SEBS, 20-50 parts white oil, 10-20 parts hydrogen-modified polypropylene, 3-5 parts modified adsorption and devolatilization aid, 24-30 parts filler, and 0.5-1 part antioxidant.

3. The method for preparing low-odor, low-emission styrene-based TPE material for automotive interiors according to claim 1, characterized in that, The preparation process of the modified adsorption aid is as follows: S1: Under a protective atmosphere, 3-methoxy-4-hydroxybenzaldehyde, 2,3-epoxypropyl methacrylate, and anhydrous ethanol were mixed and stirred until homogeneous. Tetrabutylammonium bromide was added, the temperature was raised to 85°C, and the mixture was stirred at a constant temperature for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, and the cooled solution was transferred to a low-temperature environment for crystallization. The crystallized system was filtered, the filter cake was collected, and after drying, intermediate A was obtained. S2: Under a protective atmosphere, intermediate A was added to anhydrous N,N-dimethylformamide and stirred until homogeneous. Then, γ-aminopropyltriethoxysilane solution was slowly added dropwise. After the addition was complete, the temperature was raised to 70°C and the mixture was stirred at a constant temperature for 12 hours. Then, diethyl phosphite was added, the temperature was raised to 90-85°C, and the mixture was stirred for another 14 hours. After the reaction was completed, the mixture was cooled to room temperature, and the solvent was removed by rotary evaporation. The concentrated solution was slowly added dropwise to a large amount of deionized water, and the solid precipitated. The solid was filtered, washed, and dried to obtain the modifier. S3: Activated carbon, silica, alumina, and zeolite powder were added to a mixed solvent of anhydrous ethanol and deionized water. After ultrasonic dispersion, the pH was adjusted to 4-5 with acetic acid to obtain a mixed suspension. The modifier was added to anhydrous ethanol and stirred until homogeneous. Then, it was slowly added to the mixed suspension at room temperature. After the addition was complete, the temperature was raised to 60°C and the reaction was carried out with constant temperature and stirring for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with anhydrous ethanol and deionized water in sequence, and vacuum dried to obtain the modified adsorption aid.

4. The method for preparing low-odor, low-emission styrene-based TPE material for automotive interiors according to claim 3, characterized in that, The raw materials for preparing intermediate A include the following components: by weight, 10-12 parts of 3-methoxy-4-hydroxybenzaldehyde, 9-10 parts of 2,3-epoxypropyl methacrylate, 70-80 parts of anhydrous ethanol, and 0.3-0.5 parts of tetrabutylammonium bromide.

5. The method for preparing low-odor, low-emission styrene-based TPE material for automotive interiors according to claim 3, characterized in that, The raw materials for preparing the modifier include the following components: by weight, 10-12 parts intermediate A, 60-80 parts anhydrous N,N-dimethylformamide, 18-19 parts γ-aminopropyltriethoxysilane solution, and 4-5 parts diethyl phosphite; wherein the concentration of the γ-aminopropyltriethoxysilane solution is 40 wt%.

6. The method for preparing low-odor, low-emission styrene-based TPE material for automotive interiors according to claim 3, characterized in that, The raw materials for preparing the modified adsorption aid include the following components: by weight, 30-40 parts activated carbon, 20-25 parts silica, 10-15 parts alumina, 10-15 parts zeolite powder, 180-250 parts anhydrous ethanol, 80-100 parts deionized water, and 10-12 parts modifier.

7. The method for preparing low-odor, low-emission styrene-based TPE material for automotive interiors according to claim 1, characterized in that, The devolatilization aid comprises deionized water and anhydrous ethanol in a mass ratio of 1:

1.

8. The method for preparing low-odor, low-emission styrene-based TPE material for automotive interiors according to claim 1, characterized in that, The antioxidant is one or more of B215, 1010, 1076, 1790, and 168.

9. The styrene-based TPE material obtained by the preparation method of the low-odor, low-emission styrene-based TPE material for automotive interiors according to any one of claims 1-8.